2000
DOI: 10.1080/713754381
|View full text |Cite
|
Sign up to set email alerts
|

Population lateralisation and social behaviour: A study with 16 species of fish

Abstract: We investigated turning responses in 16 species of fish faced with a vertical-bar barrier through which a learned dummy predator was visible. Ten of these species showed a consistent lateral bias to turn preferentially to the right or to the left. Species belonging to the same family showed similar directions of lateral biases. We performed an independent test of shoaling tendency and found that all gregarious species showed population lateralisation, whereas only 40% of the non-gregarious species did so. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(114 citation statements)
references
References 30 publications
6
107
1
Order By: Relevance
“…Thus, we hypothesize that the specializations of forelimb functions in red-necked wallabies have been shaped under the pressure of ecological factors. This interpretation is consistent with the general evidence for high evolutionary plasticity in motor and sensory lateralization (e.g., [35,[44][45][46][47]). …”
Section: Figure 2 Lateralization Of Forelimb Use In Marsupialssupporting
confidence: 81%
“…Thus, we hypothesize that the specializations of forelimb functions in red-necked wallabies have been shaped under the pressure of ecological factors. This interpretation is consistent with the general evidence for high evolutionary plasticity in motor and sensory lateralization (e.g., [35,[44][45][46][47]). …”
Section: Figure 2 Lateralization Of Forelimb Use In Marsupialssupporting
confidence: 81%
“…Thus, motor laterality can be the result of a selective pressure to align the direction of the asymmetries in most individuals of a social and gregarious population (Vallortigara and Rogers 2005). For example, this coordination would be very important under predation and serve to keep the flock closer together as a defensive tactic, as it has been suggested for other species (Bisazza et al 2000). Rogers and Andrew (2002) speculated on an association between left/right bias at the population level based on the valence hypothesis mentioned at the beginning: species for which survival depends on withdrawal and being more fearful of new environments should have the right hemisphere dominant over emotional and behavioural processing, as opposed to species that are adapted to a high level of exploration to survive.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies have confirmed that the eye used to look at the dummy predator in the detour test is the same as that used when viewing a real predator (Brown et al 2004(Brown et al , 2007aBisazza et al 2007). Bisazza et al (2000a) compared 16 species from different fish families in the detour test. Fishes of all 16 species were trained to escape from the same stimulus (a dip net provided with two eyes) that mimicked a predator and was used as the target stimulus in the detour test.…”
Section: Predator Evasionmentioning
confidence: 91%
“…However, empirical evidence in support of this hypothesis is equivocal. Bisazza et al (2000a) examined 16 species of fishes and found evidence that population biases were more frequent in species with a strong shoaling tendency than in solitary ones, but this finding requires confirmation using a larger sample size and correcting for phylogeny. Conversely, found no difference in schooling efficiency when comparing groups composed of female topminnow of mixed laterality (LD and RD) and groups of females with the same laterality.…”
Section: Evolutionary Significance Of Population Biases In Lateralitymentioning
confidence: 99%